Trade, Regulations, and Income - Freund, Caroline; Bolaky, Bineswaree (2012)
We examine the relationship between openness and per-capita income using cross-country data from 126 countries. We find that trade leads to a higher standard of living in flexible economies, but not in rigid economies. Business regulation, especially on firm entry, is more important than financial development, higher education, or rule of law as a complementary policy to trade liberalization. Specifically, after controlling for the standard determinants of per-capita income, our results imply that a 1% increase in trade is associated with more than a one-half percent rise in per-capita income in economies that facilitate firm entry, but has no positive income effects in more rigid economies. The findings are consistent with Schumpeterian "creative destruction", which highlights the importance of new business entry in economic performance, and with previous firm-level studies showing that the beneficial effects of trade liberalization come largely from an intra-sectoral reallocation of resources.